Trend growth and the dynamic effects of government spending - Mewael F. Tesfaselassie (Kiel Institute for the World Economy (IfW), 2011)
The paper studies the macroeconomic effects of government spending shocks in an economy characterized by positive trend growth. It shows that the lower is the trend growth rate the less inflationary are government spending shocks and vice versa. Moreover, on impact output is higher but exhibits less persistence the lower is trend growth, an effect that also characterizes consumption and the government spending multiplier, given that consumption and labor are somewhat complementary.
Keywords: E21; E62; H31; 330; Trend growth; price and wage staggering; government spending multiplier; Finanzpolitik; Öffentliche Ausgaben; Schock; Multiplikator; Wirtschaftswachstum; Preisrigidität; Lohnrigidität; Theorie